(untitled) (Tikrit Journal of Veterinary Science, 2025)
The current study was conducted to evaluate the surgical removal of iatrogenic sciatic nerve fibrosis that occurs after intramuscular injection with diclofenac sodium. A total of 20 healthy local- breed male rabbits were randomly divided into two equal groups (n=10). All rabbits underwent general anesthesia, followed by surgical exploration of the sciatic nerve in the left hind limb and injection of (1.5mg/kg) diclofenac sodium (2.5%) intraneurally to elicit an experimental iatrogenic sciatic nerve injury. All of the experimental animals was left for 14-day post operation and was divided into two groups, control groups were left without treatment, dissection group group underwent surgery to open the site of the induction surgery and removing the fibrosis from and around the sciatic nerve. For the clinical assessments, motor and sensory functions were evaluated weekly from the first week post operation until the end of the 84-day study period. Motor and sensory evaluations revealed statistically significant differences between the control group and dissection group on all of the clinical evaluation periods, the postoperative period confirmed an earlier clinical improvement in the treatment group in the knuckling sign and gait of the experimental animals with a better recovery muscle contraction force, the sensory evaluation revealed an earlier recovery and return of sensation in the dissection group when compared with the control group.